Avaliação do impacto sonoro em ciclovias na cidade de Aracaju/SE - Santos, Fábio Alves dos (2024)
The growth of the cycling system emerges as an alternative to the intense vehicle traffic in cities. However, it has brought sound exposure to cyclists from vehicle traffic noise, emerging as a significant health concern, as noise can cause stress, sleep disturbances, negative impacts on the nervous system, among others. Despite Federal Law No. 12,587 encouraging nonmotorized mobility, this research focuses on the apparent lack of consideration of the noise impact when establishing criteria for the implementation of bike lanes. Based on the reality of Aracaju/SE, this study aims to evaluate the sound impact on bike lanes, through campaigns measuring sound pressure levels and analyzing influencing factors on noise, such as physical characteristics of the bike lane and nearby surroundings and vehicle traffic. Data analysis revealed that all measurement points of the study objects exceed the noise levels allowed by specific standards - NBR 10151:2019 - and do not meet the minimum standards of the World Health Organization (WHO). Despite bike lanes meeting basic physical implementation criteria, they generally do not consider protection against traffic noise for their users. A greater distance from the source-receiver can mitigate noise levels, as observed at sampling points where, despite high traffic volume, lower noise levels were observed due to the positioning of the median, which distances the bike lane from the source of noise from vehicle traffic. The complexity of urban noise pollution, influenced by various factors, demands a detailed analysis of the contribution of different types of vehicles, suggesting complementary studies. Prevention is crucial during urban infrastructure projects, but mitigating measures, such as vehicle restrictions at certain times and traffic calming techniques, can help reduce the impact of noise on bike lanes and urban areas.